Holobiont dysbiosis or acclimatation? Shift in the microbial taxonomic diversity and functional composition of a cosmopolitan sponge subjected to chronic pollution in a Patagonian bay - Gastaldi, Marianela (2024)
Dysbiosis and acclimatization are two starkly opposing outcomes of altered holobiont associations in response to environmental pollution. This study assesses whether shifts in microbial taxonomic composition and functional profiles of the cosmopolitan sponge Hymeniacidon perlevis indicate dysbiotic or acclimatized responses to water pollution. To do so, sponge and water samples were collected in a semi-enclosed environment (San Antonio Bay, Patagonia, Argentina) from variably polluted sites (i.e., eutrophication, heavy metal contamination). We found significant differences in the microbiome of H. perlevis with respect to the pollution history of the sites. Several indicators suggested that acclimatization, rather than dysbiosis, explained the microbiome response to higher pollution: 1) the distinction of the sponge microbiome from the water microbiome; 2) low similarity between the sponge and water microbiomes at the most polluted site; 3) the change in microbiome composition between sponges from the different sites; 4) a high similarity in the microbiome among sponge individuals within sites; 5) a similar ratio of common sponge microbes to opportunistic microbes between sponges at the most and least polluted sites; and 6) a distinctive functional profile of the sponge microbiome at the most polluted site. This profile indicated a more expansive metabolic repertoire, including the degradation of pollutants and the biosynthesis of secondary metabolites, suggesting a relevant role of these microbial communities in the adaptation of the holobiont to organic pollution. Our results shed light on the rearrangement of the H. perlevis microbiome that could allow it to successfully colonize sites with high anthropogenic impact while resisting dysbiosis.